2021
DOI: 10.1007/s10802-021-00817-w
|View full text |Cite
|
Sign up to set email alerts
|

Using the 11-item Version of the RCADS to Identify Anxiety and Depressive Disorders in Adolescents

Abstract: The purpose of this study was to identify items from the Revised Children’s Anxiety and Depression Scale – RCADS-C/P that provided a brief, reliable and valid screen for anxiety and/or depressive disorders in adolescents. In addition, we examined whether adding items assessing suicidal ideation (Moods and Feelings Questionnaire – MFQ- C/P) and symptom impact and duration (items adapted from the Strengths and Difficulties Questionnaire – SDQ) improved the identification of adolescents with anxiety and/or depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Another possible concern is that the DSM-5 was used for the clinical evaluation, but the RCADS version is based on DSM-IV. A recent review of the RCADS as per DSM-5 symptoms identified the anxiety symptoms (31 items) that match the DSM-5 [40]. The subset of anxiety items in our study is within those that have been determined to match the DSM-5.…”
Section: Box 2 Example Application Of Validation Results: Adjustments...mentioning
confidence: 73%
“…Another possible concern is that the DSM-5 was used for the clinical evaluation, but the RCADS version is based on DSM-IV. A recent review of the RCADS as per DSM-5 symptoms identified the anxiety symptoms (31 items) that match the DSM-5 [40]. The subset of anxiety items in our study is within those that have been determined to match the DSM-5.…”
Section: Box 2 Example Application Of Validation Results: Adjustments...mentioning
confidence: 73%
“…It is possible that caregivers were more able to notice ‘external’ changes in behaviours but underestimated more ‘internal’ symptoms in young people (De Los Reyes et al., 2015), such as their thoughts and feelings. However, caregivers rated the more established 47-items version of the RCADS which has been shown to be sensitive to change (Chorpita et al., 2000), whereas young people rated a recently developed 11-items version which has been validated for screening purposes only (Radez et al., 2021). This shorter version was chosen to reduce demands on children with maltreatment histories who often experience cognitive difficulties (Masson et al., 2015) but it may not have been sensitive to the benefits of CFT on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses also explored the number of disorder-specific subscales in the RCADS-47 (i.e., separation anxiety, generalised anxiety, panic, social phobia, obsessive-compulsive disorder and depression) with scores that were above the clinical cut-off. Young people completed the child version of the RCADS-11, with a score range of 0–33 and a clinical cut-off of ≥14 (Radez et al., 2021). For both RCADS measures, higher scores reflected greater severity.…”
Section: Methodsmentioning
confidence: 99%
“…11-item version of the Revised Children's Anxiety and Depression Scale (RCADS) (Radez et al, 2021). We used the 11-item version of the RCADS (henceforth referred to as 'RCADS-11'), which consists of six items assessing anxiety and five items assessing depression symptoms in young people.…”
Section: Methodsmentioning
confidence: 99%